Polarized FT-IR photoacoustic spectroscopy on polymer fibers - Eichhorn,K.J; Adam,G.
The orientation of macromolecular chains in two melt-spun polymer fibers (segmented polyurethane elastomer and melt-modified polyolefine fibers)was studied by photoacoustic spectroscopy (PAS)with polarized light in the mid-infrared range. The PAS orientation functions calculated from the photoacoustic signal intensities of orientation sensitive bands describe the orientation of the different chain segments with respect to the fiber axis. Thus, the orientation of hard and soft segments in the unstressed polyurethane fiber is different and both are similiar to that of the corresponding injection molded bars. With increased spinning velocity an improved orientation of the polyolefine chains along the fiber axis, but only in the amorphous regions of the polymer, were detected. Only a slight reduction of orientation was measured as a result of the subsequent chemical crosslinking in the polyolefines.
Keywords: MOLECULAR ORIENTATION; POLARIZED FT-IR PHOTOACOUSTIC SPECTROSCOPY; POLYOLEFIN FIBERS; POLYURETHANE FIBERS; POLARIZED FT-IR PHOTOACOUSTIC SPECTROSCOPY; POLYOLEFIN FIBERS; POLYURETHANE FIBERS